A causal association between chemokines and the risk of lung cancer: a univariate and multivariate mendelian randomization study - Mengmeng Wang; Mingjun Gao; Wenbo He; Siding Zhou; Yusheng Shu; Xiaolin Wang (Journal of Cardiothoracic Surgery)
Abstract Background Observational studies and experimental evidence have shown that chemokines play important roles in lung cancer development, progression, and treatment. However, few studies have examined the causal association between them. Methods Summary data of chemokines and lung cancer were obtained from genome-wide association studies. Mendelian randomization (MR) analyses were performed by five methods, Inverse variance weighted (IVW), Weighted median estimation, MR-Egger, Simple mode and Weighted, with IVW as the primary analysis method. Sensitivity analysis was used to assess the reliability of the MR results. Multivariate Mendelian randomization studies were used to infer whether causality was influenced by potential mediators. The expression levels of CCL21 were analyzed by quantitative real-time PCR. Results We found that CCL21 was negatively associated with lung adenocarcinoma risk. CCL25 was positively associated with lung squamous cell carcinoma risk. CCL5 was negatively associated with small cell lung cancer risk. CCL21, CCL24, CCL27, and CCL28 was positively associated with small cell lung cancer risk. After multivariate Mendelian randomization adjustment for smoking behavior, it was found that the effect of CCL25 on lung squamous cell cancer disappeared, and the effect of CCL21 on small cell lung cancer was quite opposite to the univariate. The receiver operating characteristic curve indicated that chemokines had high accuracy in the diagnosis of lung cancer. CCL21 expression levels showed large differences in lung adenocarcinoma cells. Conclusion These results highlighted the causal effects of chemokines on lung cancer and suggested a mediating role of smoking behavior in the association between chemokines and lung cancer.